Development of an orthotopic canine prostate cancer model expressing human GRPr. Issue 14 (11th July 2018) - Tweedle, Michael F.; Ding, Haiming; Drost, William T.; Dowell, Joshua; Spain, James; Joseph, Mathew; Elshafae, Said M.; Menendez, Maria‐Isabela; Gong, Li; Kothandaraman, Shankaran; Dirksen, Wessel P.; Wright, Chadwick L.; et al.
Abstract : Background: Ace‐1 canine prostate cancer cells grow orthotopically in cyclosporine immunosuppressed laboratory beagles. We previously transfected (human Gastrin‐Releasing Peptide Receptor, huGRPr) into Ace‐1 cells and demonstrated receptor‐targeted NIRF imaging with IR800‐G‐Abz4‐t‐BBN, an agonist to huGRPr. Herein, we used the new cell line to develop the first canine prostate cancer model expressing a human growth factor receptor. Methods: Dogs were immunosuppressed with cyclosporine, azathioprine, prednisolone, and methylprednisolone. Their prostate glands were implanted with Ace‐1 huGRPr cells. The implantation wounds were sealed with a cyanoacrylic adhesive to prevent extraprostatic tumor growth. Intraprostatic tumors grew in 4‐5 week. A lobar prostatic artery was then catheterized via the carotid artery and 25‐100 nmol IR800‐Abz4‐t‐BBN was infused in 2 mL followed by euthanasia in dogs 1‐2, and recovery for 24 h before euthanasia in dogs 3‐6. Excised tissues were imaged optically imaged, and histopathology performed. Results: Dog1 grew no tumors with cyclosporine alone. Using the four drug protocol, Dogs 2‐6 grew abundant 1‐2 mm intracapsular and 1‐2 cm intraglandular tumors. Tumors grew >5 cm when the prostate cancer cells became extracapsular. Dogs 4‐6 with sealed prostatic capsule implantation sites had growth of intracapsular and intraglandular tumors and LN metastases at 5 weeks. High tumor to background BPH signal in the NIRF images of sectioned prostate glands resulted from the 100 nmol dose (∼8 nmol/kg) in dogs 2‐4 and 50 nmol dose in dog 5, but not from the 25 nmol dose in Dog 6. Imaging of mouse Ace‐1 huGRPr tumors required an intravenous dose of 500 nmol/kg body wt. A lymph node that drained the prostate gland was detectable in Dog 4. Histologic findings confirmed the imaging data. Conclusion: Ace‐1 huGRPr cells created viable, huGRPr‐expressing tumors when implanted orthotopically into immune‐suppressed dogs. Local delivery of an imaging agent through the prostatic artery allowed a very low imaging dose, suggesting that therapeutic agents could be used safely for treatment of early localized intraglandular prostate cancer as adjuvant therapy for active surveillance or focal ablation therapies, or for treating multifocal intraglandular disease where focal ablation therapies are not indicated or ineffective.